Radiation‐induced morphea of the breast-A case series - Paula Finnegan; Lisa Kiely; Catriona Gallagher; Sarah Ni Mhaolcatha; Linda Feeley; Jim Fitzgibbon; Jessica White; John Bourke; Lesley Ann Murphy (Wiley, 2023)
Abstract Radiation‐induced morphea (RIM) is a rare but recognized late complication of radiotherapy. It was first described in 1905, not long after the initial discovery of X‐rays by Roentgen. Characterized by the deposition of excess collagen in the dermis, it results in thickening of the skin. Its frequency is approximately 2 in 1000. We present a series of three cases involving patients receiving radiotherapy treatment for breast cancer, each of which subsequently developed RIM. Because of its rarity, RIM is often misdiagnosed as infection or metastatic disease. This can lead to delayed diagnosis and treatment, leading to poorer outcomes such as chronic pain issues. Early dermatological involvement and tissue sampling to examine histopathological features can avoid this, leading to better care and improved results. A variety of treatment options are available, ranging from topical to systemic, with early induction more likely to result in a positive response.